Tìm đa thức M biết: $M$+ ($5$$x^{2}$ – $2$$x$$y$) = $6$$x^{2}$ + $9$$x$$y$ – $y^{2}$ 24/08/2021 Bởi Valerie Tìm đa thức M biết: $M$+ ($5$$x^{2}$ – $2$$x$$y$) = $6$$x^{2}$ + $9$$x$$y$ – $y^{2}$
`M+(5x^2-2xy)=6x^2+9xy-y^2` `<=> M=6x^2+9xy-y^2-(5x^2-2xy)` `<=> M=6x^2+9xy-y^2-5x^2+2xy` `<=> M=x^2+11xy-y^` Bình luận
$ M + (5x^2 -2xy) = 6x^2 +9xy – y^2$ $\to M = ( 6x^2 +9xy – y^2 ) – (5x^2 -2xy)$ $\to M = 6x^2 +9xy – y^2 – 5x^2 +2xy$ $ \to M = (6x^2 -5x^2) + (9xy +2xy) – y^2$ $\to M = x^2 +11xy – y^2$ Vậy $ M =x^2 +11xy – y^2$ Bình luận
`M+(5x^2-2xy)=6x^2+9xy-y^2`
`<=> M=6x^2+9xy-y^2-(5x^2-2xy)`
`<=> M=6x^2+9xy-y^2-5x^2+2xy`
`<=> M=x^2+11xy-y^`
$ M + (5x^2 -2xy) = 6x^2 +9xy – y^2$
$\to M = ( 6x^2 +9xy – y^2 ) – (5x^2 -2xy)$
$\to M = 6x^2 +9xy – y^2 – 5x^2 +2xy$
$ \to M = (6x^2 -5x^2) + (9xy +2xy) – y^2$
$\to M = x^2 +11xy – y^2$
Vậy $ M =x^2 +11xy – y^2$